Landslides and flood hazard mapping using geomorphological methods in Santa Ana, Costa Rica - Acosta Quesada, Marco (2024)
This study addresses the critical need for comprehensive hazard maps to guide urban and periurban risk management in Santa Ana, Costa Rica. Located near the capital, San Jose, Santa Ana is a rapidly developing municipality characterized by high-value properties, commercial zones, luxury housing, agricultural, and protected areas. However, it faces significant challenges from landslides and floods. Despite its vulnerability, the municipality lacks detailed, holistic hazard assessments. To bridge this gap, we employed geomorphological methods, including morphometry and morphogenetics, integrated with geographic information systems (GIS), historical data, and onsite validation. Our analysis identified that slopes exceeding 20° are particularly susceptible to landslides, with valleys and unstable hillslopes being critical zones for seismic and water-induced destabilization. For flood hazards, areas with low slope and high flow accumulation, such as alluvial fans and flood plains, were found to be highly susceptible. Field and mapping validation against the DesInventar disaster database confirmed the accuracy of our hazard zones. These findings provide essential geospatial insights for effective risk management, decision-making, and territorial planning, enabling proactive and adaptive responses to natural hazards in Santa Ana. While this study does not present radical methodological innovations, its main contribution lies in demonstrating how easy-access and practical geomorphological tools can be used to generate valuable information on risk zoning in regions with limited resources. Furthermore, the methodology and insights from this study are applicable to other urban and periurban regions facing similar geomorphic hazards, highlighting its broader relevance.